Penerapan Metode Pieces Framework Dalam Analisis Tingkat Kepuasan Pengguna Layanan Aplikasi Livin by Mandiri - Susanti Susanti; Dila Seltika Canta; Elvin Leander Hadisaputro (STMIK Budi Darma, 2022)
Livin by Mandiri is an official mobile banking application from Bank Mandiri to make it easier for customers to get online banking services. The Livin by Mandiri application can be installed on user smartphones such as IOS and Android. Users only need to connect and access Livin by Mandiri, then all banking matters can be completed in minutes and there are many menus provided in the Livin by Mandiri application such as transfers, payments, top-ups, e-money, cash withdrawals, QR, E-mail. Wallet, savings and time deposit info. With the Livin by Mandiri application, it is necessary to identify problems to find out how satisfied users are with Livin by Mandiri. The method that can be used in evaluating it is by using the PIECES method (Performance, Information, Economic, Control and security, Efficiency, Service). Based on the PIECES method in measuring the level of satisfaction with users of the Livin By independent application. This study aims to measure the level of user satisfaction with the system applied. Based on the results of the average calculation with the domains of Performance, Information & Data, Economics, Control & Security, Efficiency, and Service, the satisfaction level was obtained with a value of 4.29 which means that the use of Livin by Mandiri Application services in the North Penajam Paser Regency area can be concluded that the level of service users' satisfaction with the Livin by Mandiri application is included in the VERY SATISFIED category